Oxygen isotopic composition of ice samples from the Hells Gate and Backstairs Passage ice shelves (Northern Victoria Land, Antarctica): evidence for bottom freezing. - BARONI, CARLO; STENNI B; IACUMIN P. (1991)
During the 1986/87 and 1987/88 Italian Antarctic expeditions a number of ice samples were col~ected f~om different locations. Sixty-five samples coming mainly from the Hells Gate and Backstairs Passage ice shelves have been studied for their -oxygen isotopic composition. Very negative <5 180 values are characteristic of continental snowfall in Antarctica /(aroun.fl:-21±3 per mil for snow deposited near the coastal area). The <5180 values obtained from seawater edge ice and ice beneath dirt cones range from -0.80 to +2.66 per mil, suggesting that the origin of this ice is essentially from seawater freezing. This is also proven by the finding of shells and skeletons of I?arine organisms included in the ice and is in agreement with the conclusions of previous studies on Antarctic ice shelves. Ice samples from the upper section of dirt cones show <5 180 values from -12.68 to -6.15 per mil, which are intermediate between those of seawater ice and continental ice. These values are probably explained by the mixing of water from the melting of the snowdrift ice capping the cones and the seawater ice forming their main body. The ice core of the moraine of Corner Glacier, further inland, shows <5 180 values from -31.81 to -26.40, in agreement with a continental origin of the ice. This ice is clearly formed by snow which fell at higher elevations, as proven by the remarkable 180 depletion of these samples as compared to local snowfall. It is apparent that the origin of ice can be well identified by isotope measurements, irrespective of sample location and appearance.